Discharge estimation for equatorial natural rivers with overbank flow - Law, Puong Ling; Lai, Sai Hin; Nabil, Bessaih; Aminuddin, Ab Ghani (Taylor and Francis Ltd., 2008)
The estimation of discharge capacity in river channels is complicated by variations in geometry and boundary roughness. Estimating flood flows is particularly difficult because of compound cross-sectional geometries and because of the difficulties of flow gauging. Results are presented of a field study including the stage-discharge relationships and surface roughness in term of the Darcy-Weisbach friction factor, fa for several frequently flooded equatorial natural rivers. Equations are presented giving the apparent shear force acting on the vertical interface between the main channel and floodplain. The resulted apparent friction factor, fa is shown to increase rapidly for low relative depth. A method for predicting the discharge of overbank flow of natural rivers is then presented, by means of a composite friction, fc, which represents the actual resistance to flow due to the averaged boundary shear force and the apparent shear force. Equations are also presented giving the composite friction factor from easily calculated parameters for overbank flow of natural rivers. The results obtained using the methods proposed show that a significant improvement has been achieved compare to the discharge obtained using traditional methods, with an averaged error of 2.7%.